68.6k views
11 votes
Let f(x) = 4x - 7 and g(x) = x +5. Find f(g(x)) and g(f(x))

f(g(x))=(Simplify your answer.)
g(f(x)) = (Simplify your answer.)
=
)

1 Answer

4 votes

Explanation:

Given:

  • f(x) = 4x - 7 and g(x) = x + 5

Find f(g(x)) and g(f(x)):

  • f(g(x)) = f(x + 5) = 4(x + 5) - 7 = 4x + 20 - 7 = 4x + 13
  • g(f(x)) = g(4x - 7) = 4x - 7 + 5 = 4x - 2
User CovertIII
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.